FAKTOR-FAKTOR PENYEBAB PERUBAHAN TRADISI SILAT DALAM ADAT PERNIKAHAN PADA MASYARAKAT MUARA LEMBU KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Tia Nopriantari; Hambali Hambali; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Abstract: Abstract: This research is motivated by the factors that cause changes in the tradition of silat in marriage customs in the muara lembucommunity of the singingi sub-district of Kuantan singingi district, where this silat is usually carried out in a traditional wedding but today the tradition is very rarely carried out by the estuary of the ox. The formulation of the problem in this study is "what are the factors that cause changes in the silat tradition in marriage customs in the Muara Lembu community, Singingi District, Kuantan Singingi District". This study aimed at determine the factors that cause changes in the tradition of silat in the customs of marriage in the Muara Lembu District community. Singingi Regency of Kuantan Singingi. Data collection techniques in this study were observation, interviews and documentation. The respondents of this study were 7 people: 2 ninik mamak, 1 silat trainer, 2 silat players and 2 community members. Data analysis techniques in this study used descriptive qualitative methods. The results in this study are that there are 2 factors that cause changes in the tradition of silat in the custom of marriage in the estuary community of the cattle singing district of Kuantan singingi district, namely external factors and internal factors. External factors are the influence of other cultures and internal factors, namely: the discovery of new discoveries as well as the increase and decrease in population.Key Words: Factors That Cause Change, Silat Tradition